LEGISLATIVE AND REGULATORY GOVERNANCE OF DEPARTMENTAL MEDICINE IN UKRAINE - Kryzyna N. P.; Sukhanova Y. A. (International Journal of Innovative Technologies in Social Science, 2021)
The need for effective reform of the health care system and departmental medicine is due to Ukraine’s integration into the community of European states and its accession to NATO’s International Alliance. This is possible through the development and implementation of effective management mechanisms. The study highlights the causes, features of the formation and functioning of departmental medicine in Ukraine, identifies mechanisms and problems of public administration in this area, their causes and possible solutions using methods of abstraction, systems analysis and structural modeling. The civil and military sectors of departmental medicine are defined and the scheme of subordination of divisions is described, achievements of reform of departmental medicine in the context of reforming of the Ukrainian health care system are investigated. Based on the analysis of the contradictions of research on this problem in the articles of foreign and domestic scientists in various fields and comparative analysis of the existing legal framework identified trends in reforming military and civilian departmental medicine in Ukraine and achieving their reform in other countries. Ways to improve the mechanisms of public administration, structural models of organization and prospects for further development of this medical field are proposed.